1976
DOI: 10.1289/ehp.761879
|View full text |Cite
|
Sign up to set email alerts
|

Critical periods for behavioral anomalies in mice.

Abstract: hile mice have been used less frequently than rats in behavioral research, their use has some advantages in teratological studies. The development of the mouse CNS has been investigated more extensively than that of the rat. Since time of insult has been found to be an important factor in effects on both anatomy and behavior, data on the sequence of events in CNS development are valuable in planning and interpreting behavioral assessments of potential teratogens. A comparison of studies in mice and rats sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1976
1976
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…It is unclear whether the prenatal exposure to these mixtures has been linked to reduced fetal and postnatal growth, neurological deficits, delayed development of motor functions, and impaired short-term memory (Kodavanti 2005;Seegal 2000;Seegal, Pappas, and Park 1998). The developmental processes, including neurogenesis, migration, synaptogenesis, gliogenesis, and myelination, are extremely susceptible to damage from exposure to environmental insult (Garman et al 2001;Tilson 2000;Rodier, Reynolds, and Roberts 1979;Rodier 1976). These sequences of events are genetically programmed and interference at any stage may alter subsequent development and result in permanent impairment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unclear whether the prenatal exposure to these mixtures has been linked to reduced fetal and postnatal growth, neurological deficits, delayed development of motor functions, and impaired short-term memory (Kodavanti 2005;Seegal 2000;Seegal, Pappas, and Park 1998). The developmental processes, including neurogenesis, migration, synaptogenesis, gliogenesis, and myelination, are extremely susceptible to damage from exposure to environmental insult (Garman et al 2001;Tilson 2000;Rodier, Reynolds, and Roberts 1979;Rodier 1976). These sequences of events are genetically programmed and interference at any stage may alter subsequent development and result in permanent impairment.…”
Section: Introductionmentioning
confidence: 99%
“…These sequences of events are genetically programmed and interference at any stage may alter subsequent development and result in permanent impairment. In adults, they have generally reached a steady state and are not potential targets for neurotoxic agents (Garman et al 2001;Tilson 2000;Campbell et al 1997;Rodier, Reynolds, and Roberts 1979;Rodier 1976). Extensive studies using lead, mercury, methylazoxymethanol, alcohol, methylmercury, nicotine, and chlorpyrifos have shown that these chemicals affect multiple pathways during normal development (Erickson and Talts 2000;Campbell et al 1997;Chanda and Pope 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Chemicalinduced neurodevelopmental effects could depend on variables such as changes in environmental temperature, hormonal status, and life-cycle stage. Neurotoxicity following developmental exposure to chemicals can vary qualitatively and quantitatively depending on the phase of nervous system maturation (4,5). Thus, a chemical could affect neurodevelopmental processes if exposure occurred during a critical period of neuroendocrine maturation, but have little or no effect if exposure occurred at some other period of development.…”
Section: Neurodevelopmental Effects Of Endocrine Disruptorsmentioning
confidence: 99%
“…Neurogenesis, migration, synaptogenesis, gliogenesis, and myelination are developmental processes that have generally reached a steady state in the adult and are not potential targets for neurotoxic agents. There are several examples in the literature demonstrating that exposure to a chemical during a critical period of development will produce neurotoxicity, whereas exposure to the same chemical during adulthood will have little or no effect (4)(5)(6).…”
mentioning
confidence: 99%
“…This reflects the rapid proliferation of neural tissue during early development and the establishment of functional synaptic contacts as the brain matures. In regard to the former process, i.e., cell proliferation, data on actual periods of maximum proliferation of neurons comprising different regions in the brain of the rat and mouse are summarized in this session's paper by Rodier (12) and indicate that neural proliferation in some brain areas continues for some time after birth. As the proliferation process ends, however, functional brain capacity probably begins to reach as asymptote, likely sometime not long after puberty, and is seen in the present scheme as leveling off for a prolonged period during adulthood.…”
Section: Relative Functional Brain Capacitymentioning
confidence: 99%